Anti-crack impervious concrete and preparation method thereof
Through the synergistic effect of modified steel fiber and sepiolite fiber, the problems of concrete cracking and decreased impermeability at high temperatures are solved, the mechanical properties and durability of concrete are improved, and the bonding strength between fiber and concrete is enhanced.
Patent Information
- Application Number
- CN202510946478.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2025-10-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing concrete is prone to cracking at high temperatures, and the corrosion of steel fibers and the melting of polypropylene fibers lead to a decrease in anti-permeability performance. In addition, the bonding strength between steel fibers and concrete is low, making it difficult to effectively enhance the structural strength and durability of concrete.
The synergistic effect of modified steel fiber and modified sepiolite fiber is adopted. The surface of the sepiolite fiber is treated with γ-aminopropyltriethoxysilane and graphene oxide is adsorbed. The surface of the steel fiber is treated with modified glue to enhance the bonding strength between the fiber and concrete, and form a wear-resistant transfer layer on the surface of the sepiolite fiber.
It improves the compressive strength, flexural strength, crack resistance and anti-seepage performance of concrete, enhances the interfacial bonding performance between fiber and concrete, prevents steel fiber from rusting, and improves the mechanical properties and durability of concrete.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and particularly relates to crack-resistant and anti-seepage concrete and a preparation method thereof. Background Art
[0002] With the strengthening of my country's infrastructure and the increasing number of construction projects, the use of large-volume concrete is becoming more and more widespread. However, concrete cracking has become increasingly prominent, seriously affecting the structural strength, durability, and volume stability of concrete. Furthermore, once cracking occurs in concrete, even if it is not clearly visible on the surface, the bonding density of the internal components is damaged, which directly affects the concrete's impermeability.
[0003] Fiber-reinforced concrete-based materials are increasingly being used in transportation tunnels, bridges, and other construction structures due to their excellent tensile, flexural, crack, fatigue, and impact resistance. Currently, the most widely used fibers for improving the performance of concrete-based materials are steel fibers and polypropylene fibers. However, steel fibers severely rust at temperatures above 600°C, and polypropylene fibers melt at around 170°C. The resulting pores make the matrix more susceptible to cracking, significantly reducing or even completely losing tensile properties. Furthermore, steel fibers have a smooth surface and low surface energy, making it difficult to form a strong bond with the concrete-based material. Furthermore, steel fibers have a low strength utilization rate, and when the structure is damaged, the failure often manifests as brittle failure of the concrete base. Summary of the Invention
[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a crack-resistant and anti-seepage concrete and a preparation method thereof. Through the synergistic effect of modified steel fiber and modified sepiolite fiber, the prepared concrete has high compressive strength and flexural strength, and good crack resistance and anti-seepage performance.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A crack-resistant and anti-seepage concrete comprises the following raw materials in parts by weight: 100-150 parts of cement, 10-40 parts of silica fume, 30-50 parts of fly ash, 100-150 parts of fine aggregate, 10-20 parts of modified steel fiber, 5-15 parts of modified sepiolite fiber, 2-7 parts of water reducer, and 40-80 parts of water; The modified steel fiber is prepared by pre-treating the steel fiber surface with a sodium hydroxide solution, then impregnating the steel fiber surface with a modified adhesive and thermally curing the modified adhesive. The modified adhesive is prepared by using ethyl orthosilicate and aluminum chloride hexahydrate as raw materials to provide silicon and aluminum sources respectively, and using ethanol and water to prepare silica sol and aluminum sol and mix them. The modified sepiolite fiber is prepared by pre-treating the surface of the sepiolite fiber by grafting gamma-aminopropyltriethoxysilane, and then adsorbing graphene oxide on the surface of the sepiolite fiber by an electrostatic self-assembly method.
[0006] Preferably, the cement is any one of P·O42.5 grade ordinary Portland cement and P·O52.5 grade ordinary Portland cement; the fine aggregate is river sand with a fineness modulus between 2.4 and 2.8; and the water reducer is any one of polycarboxylic acid water reducer, naphthalene water reducer, and sulfonate water reducer.
[0007] Preferably, the preparation method of the modified sepiolite fiber comprises the following steps: A. Add γ-aminopropyltriethoxysilane to a mixture of deionized water and anhydrous ethanol, stir at 35-45° C. for 2-3 hours to prepare a silane hydrolyzate, then add sepiolite fiber to the silane hydrolyzate, continue stirring for 1.5-2 hours, then take out and dry to prepare pretreated sepiolite fiber; B. Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide dispersion, then adding pretreated sepiolite fiber and adjusting the pH value of the system to 3-4 with hydrochloric acid. The mixture was reacted at 75-85°C for 2-3 hours. After the reaction was completed, the mixture was washed with deionized water and finally heat-treated at 150-165°C for 10-12 hours to prepare modified sepiolite fiber.
[0008] Preferably, in step A, the addition ratio of deionized water, anhydrous ethanol and γ-aminopropyltriethoxysilane is 30 mL:70 mL:1.5-2 g; and the addition ratio of the sepiolite fiber and silane hydrolyzate is 5-5.5 g:100 mL.
[0009] Preferably, in step B, the addition ratio of graphene oxide and deionized water is 0.1-0.15 g:100 mL; and the addition ratio of the pretreated sepiolite fiber and graphene oxide dispersion is 2-2.5 g:100 mL.
[0010] Preferably, the preparation method of the sepiolite fiber comprises the following steps: (1) Ultrasonic dispersion of sepiolite in water, allowing it to soak for 20-24 hours, followed by magnetic stirring for 1-3 hours, allowing it to settle naturally, and filtering the upper suspension, washing it with water, and drying it to obtain crude purified sepiolite; (2) Crude sepiolite was mixed with 3 mol / L hydrochloric acid at a solid-liquid ratio of 1:50, and 20% oxalic acid was added. After stirring, the mixture was placed in an autoclave and subjected to hydrothermal reaction at 190-205°C for 8-9 hours to prepare acidified sepiolite. (3) Freeze the hydrous acidified sepiolite at -20°C to form a solid, thaw it and ultrasonicate it for 0.5-1h, repeat freeze-thaw for more than three times, then wash it until it is neutral, dry it in an oven to constant weight, and then grind it in a grinding jar to make it fluffy, loosen the agglomerated fiber bundles, and prepare sepiolite fiber.
[0011] Preferably, the method for preparing the modified steel fiber comprises the following steps: ① Prepare a mixed solution of ethyl orthosilicate, ethanol and water, and then place it in a water bath at 45-55°C and stir for 4-5 hours to obtain silica sol; ② Prepare a mixed solution of aluminum chloride hexahydrate, ethanol, and water, and then place it in a water bath at 45-55°C and stir for 4-5 hours to obtain aluminum sol; ③ Mix the silica sol and aluminum sol, place in a water bath at 45-55°C and stir for 2-3 hours to obtain a modified glue solution; ④ Pretreat the surface of the steel fiber with sodium hydroxide solution, then soak the pretreated steel fiber in the modified adhesive for 10-30 minutes, then slowly pull the steel fiber out of the modified adhesive at a pulling rate of 1-2 mm / s, finally let it stand to air dry and place it in an oven at 100-120°C for thermal curing for 1-3 hours to prepare the modified steel fiber.
[0012] Preferably, in step ①, the mass ratio of ethyl orthosilicate, ethanol and water is 10:2:1; in step ②, the mass ratio of aluminum chloride hexahydrate, ethanol and water is 14:10:10.
[0013] Preferably, the mass ratio of silica sol to alumina sol in step ③ is 7:2.
[0014] A method for preparing crack-resistant and anti-seepage concrete comprises the following steps: weighing raw materials in parts by weight, adding cement, silica fume, fine aggregate, modified steel fiber and modified sepiolite fiber into a mixer, stirring and mixing, then adding water, fly ash and a water reducing agent, stirring evenly, and preparing the crack-resistant and anti-seepage concrete.
[0015] Beneficial effects of the present invention: The present invention uses γ-aminopropyltriethoxysilane to perform surface grafting pretreatment on sepiolite fiber, and then adsorbs graphene oxide on the surface of the sepiolite fiber through an electrostatic self-assembly method to prepare modified sepiolite fiber, wherein the sepiolite fiber is resistant to high temperatures, has thermal insulation, is environmentally friendly, and is low in price. The modified sepiolite fiber is doped with modified steel fiber to play a supporting role, preventing concrete from shrinking, collapsing, and cracking. The graphene oxide forms a wear-resistant transfer layer on the surface of the sepiolite fiber, and the graphene oxide grafted on the surface of the sepiolite fiber can delay the relative movement between the sepiolite fiber and concrete under load, thereby making the concrete obtain greater mechanical strength. In addition, the present invention uses ethyl orthosilicate and aluminum chloride hexahydrate as raw materials to provide silicon source and aluminum source respectively, uses ethanol and water to prepare silica sol and aluminum sol respectively, and then mixes the silica sol and aluminum sol to obtain a modified adhesive solution. The surface of the steel fiber after alkali washing contains more hydroxyl groups, which makes it easier for the modified adhesive solution to form a chemical bond with the surface of the steel fiber, strengthens the bonding strength between the two, and plays a role in enhancing the interfacial bonding performance between the steel fiber and the concrete matrix. The modified sol forms a coating layer on the surface of the steel fiber, effectively hinders the corrosion of the steel fiber, and at the same time can increase the roughness of the steel fiber surface, effectively fill the internal pores of the concrete, and improve the density of the concrete, thereby enhancing the mechanical properties and durability of the concrete. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0017] The steel fibers in the embodiments of the present invention and the comparative examples were produced by Wanfeng Abrasives & Grinding Tools Co., Ltd. and were double-ended hook-shaped with a length of 35 mm, a diameter of 0.75 mm, an aspect ratio of 45 mm, a tensile strength of 1000 MPa, and an elastic modulus of 200 GPa.
[0018] Example 1 A method for preparing sepiolite fiber comprises the following steps: (1) 1 g of sepiolite was ultrasonically dispersed in 10 mL of water, allowed to stand for 24 h, then magnetically stirred for 2 h, allowed to stand for natural sedimentation, the upper suspension was filtered, washed with water, and then dried to prepare crude purified sepiolite; (2) Crude sepiolite was mixed with 3 mol / L hydrochloric acid at a solid-liquid ratio of 1:50, and 20% oxalic acid was added. After stirring, the mixture was placed in an autoclave and subjected to hydrothermal reaction at 200°C for 8 h to prepare acidified sepiolite. (3) Freeze the hydrous acidified sepiolite at -20°C to form a solid, thaw it and ultrasonicate it for 0.5h, freeze and thaw it repeatedly for more than three times, then wash it until it is neutral, dry it in an oven to a constant weight, and then grind it in a grinding jar to make it fluffy, loosen the agglomerated fiber bundles, and prepare sepiolite fiber.
[0019] Example 2 A method for preparing modified sepiolite fiber comprises the following steps: A. Add 1.5 g of γ-aminopropyltriethoxysilane to a mixture of 30 mL of deionized water and 70 mL of anhydrous ethanol, stir at 40° C. for 3 h to prepare a silane hydrolyzate, then add 5 g of sepiolite fiber to 100 mL of the silane hydrolyzate, continue stirring for 2 h, and then take out and dry to prepare a pretreated sepiolite fiber; B. Take 0.5 g of graphene oxide and ultrasonically disperse it in 500 mL of deionized water to obtain a graphene oxide dispersion, then add 10 g of pretreated sepiolite fiber and use hydrochloric acid to adjust the pH value of the system to 3. Place it at 80°C for 2 hours. After the reaction is completed, wash it with deionized water and finally place it at 160°C for 12 hours to prepare modified sepiolite fiber.
[0020] Example 3 A method for preparing modified steel fiber comprises the following steps: ① Prepare a mixed solution of ethyl orthosilicate, ethanol and water in a mass ratio of 10:2:1, and then stir in a water bath at 50°C for 4 hours to obtain silica sol; ② Prepare a mixed solution of aluminum chloride hexahydrate, ethanol and water in a mass ratio of 14:10:10, and then stir in a water bath at 50°C for 4 hours to obtain aluminum sol; ③ Mix silica sol and aluminum sol in a mass ratio of 7:2, place in a water bath at 50°C and stir for 2 hours to obtain a modified glue solution; ④ The surface of the steel fiber was pretreated with a 2 mol / L sodium hydroxide solution, and then the pretreated steel fiber was immersed in the modified adhesive for 15 min. The steel fiber was then slowly pulled out of the modified adhesive at a pulling rate of 1 mm / s. Finally, it was allowed to air dry and placed in an oven at 100 °C for thermal curing for 3 h to prepare the modified steel fiber.
[0021] Example 4 A crack-resistant and anti-seepage concrete comprises the following raw materials in parts by weight: 110 parts of cement, 12 parts of silica fume, 33 parts of fly ash, 105 parts of fine aggregate, 10 parts of modified steel fiber prepared in Example 3, 6 parts of modified sepiolite fiber prepared in Example 2, 3.5 parts of water reducer, and 45 parts of water, wherein the cement is P·O52.5 grade ordinary Portland cement, the silica fume has a loss on ignition of 4%, the fly ash is Class F Grade I, the fine aggregate is river sand with a fineness modulus of 2.5, and the water reducer is a polycarboxylate water reducer.
[0022] The preparation method of the anti-cracking and anti-seepage concrete comprises the following steps: weighing the raw materials, adding cement, silica fume, fine aggregate, modified steel fiber and modified sepiolite fiber into a stirrer, stirring and mixing, then adding water, fly ash and water reducing agent, and stirring uniformly to prepare the anti-cracking and anti-seepage concrete.
[0023] Example 5 An anti-cracking and anti-seepage concrete comprises the following raw materials by weight: 127 parts of cement, 23 parts of silica fume, 41 parts of fly ash, 125 parts of fine aggregate, 14 parts of modified steel fiber prepared in Example 3, 10 parts of modified sepiolite fiber prepared in Example 2, 5.5 parts of water reducing agent, and 65 parts of water, wherein the cement is P·O 52.5 grade ordinary portland cement, the silica fume has a loss on ignition of 4%, the fly ash is F-class I grade, the fine aggregate is river sand with a fineness modulus of 2.5, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0024] The preparation method of the anti-cracking and anti-seepage concrete is the same as that in Example 4.
[0025] Example 6 An anti-cracking and anti-seepage concrete comprises the following raw materials by weight: 144 parts of cement, 36 parts of silica fume, 47 parts of fly ash, 148 parts of fine aggregate, 18 parts of modified steel fiber prepared in Example 3, 13 parts of modified sepiolite fiber prepared in Example 2, 6.8 parts of water reducing agent, and 77 parts of water, wherein the cement is P·O 52.5 grade ordinary portland cement, the silica fume has a loss on ignition of 4%, the fly ash is F-class I grade, the fine aggregate is river sand with a fineness modulus of 2.5, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0026] The preparation method of the anti-cracking and anti-seepage concrete is the same as that in Example 4.
[0027] Comparative Example 1 An anti-cracking and anti-seepage concrete comprises the following raw materials by weight: 144 parts of cement, 36 parts of silica fume, 47 parts of fly ash, 148 parts of fine aggregate, 18 parts of steel fiber, 13 parts of modified sepiolite fiber prepared in Example 2, 6.8 parts of water reducing agent, and 77 parts of water, wherein the cement is P·O 52.5 grade ordinary portland cement, the silica fume has a loss on ignition of 4%, the fly ash is F-class I grade, the fine aggregate is river sand with a fineness modulus of 2.5, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0028] The preparation method of the anti-cracking and anti-seepage concrete is the same as that in Example 4.
[0029] Comparative Example 2 A crack-resistant and anti-seepage concrete comprises the following raw materials in parts by weight: 144 parts of cement, 36 parts of silica fume, 47 parts of fly ash, 148 parts of fine aggregate, 18 parts of modified steel fiber prepared in Example 3, 13 parts of sepiolite fiber prepared in Example 1, 6.8 parts of water reducer, and 77 parts of water, wherein the cement is P·O52.5 grade ordinary Portland cement, the silica fume has a loss on ignition of 4%, the fly ash is Class F Grade I, the fine aggregate is river sand with a fineness modulus of 2.5, and the water reducer is a polycarboxylate water reducer.
[0030] The preparation method of the above-mentioned crack-resistant and anti-seepage concrete is the same as that of Example 4.
[0031] Comparative Example 3 A crack-resistant and anti-seepage concrete comprises the following raw materials in parts by weight: 144 parts of cement, 36 parts of silica fume, 47 parts of fly ash, 148 parts of fine aggregate, 18 parts of modified steel fiber prepared in Example 3, 6.8 parts of water reducer, and 77 parts of water, wherein the cement is P·O52.5 grade ordinary Portland cement, the silica fume has a loss on ignition of 4%, the fly ash is Class F Grade I, the fine aggregate is river sand with a fineness modulus of 2.5, and the water reducer is a polycarboxylate water reducer.
[0032] The preparation method of the above-mentioned crack-resistant and anti-seepage concrete is the same as that of Example 4.
[0033] Performance testing The crack-resistant and anti-seepage concrete prepared in Examples 4-6 and Comparative Examples 1-3 were prepared into specimens. The compressive strength and flexural strength of each specimen after curing for 28 days were tested according to GB / T 50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The anti-seepage performance of the concrete samples was tested using the water seepage height method in GB / T 50082-2009. Specifically, the concrete samples were pressurized to 1.2 MPa after sealing, and the water mark height was measured after 24 hours. The total crack area per unit area was calculated according to GB / T 50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" 24 hours after pouring. In the test, each group of specimens was prepared into a concrete sample with a length, width and height of 100 mm. The data results are shown in Table 1.
[0034] Table 1 Sample performance test results
[0035] As can be seen from the data in Table 1, the concrete samples prepared in Examples 3-5 of the present invention exhibit higher compressive and flexural strengths, as well as better crack resistance and anti-seepage properties, than those in Comparative Examples 1-3. In Comparative Example 1, the steel fibers were not modified, in Comparative Example 2, the sepiolite fibers were not modified, and in Comparative Example 3, no modified sepiolite fibers were added. This indicates that the modified steel fibers and modified sepiolite act synergistically, significantly improving the overall performance of the concrete samples.
[0036] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0037] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention, and such changes and modifications fall within the scope of the invention as claimed.
Claims
1. A crack-resistant and anti-seepage concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 100-150 parts of cement, 10-40 parts of silica fume, 30-50 parts of fly ash, 100-150 parts of fine aggregate, 10-20 parts of modified steel fiber, 5-15 parts of modified sepiolite fiber, 2-7 parts of water reducer, and 40-80 parts of water; The modified steel fiber is prepared by pre-treating the steel fiber surface with a sodium hydroxide solution, then impregnating the steel fiber surface with a modified adhesive and thermally curing the modified adhesive. The modified adhesive is prepared by using ethyl orthosilicate and aluminum chloride hexahydrate as raw materials to provide silicon and aluminum sources respectively, and using ethanol and water to prepare silica sol and aluminum sol and mix them. The modified sepiolite fiber is prepared by pre-treating the surface of the sepiolite fiber by grafting gamma-aminopropyltriethoxysilane, and then adsorbing graphene oxide on the surface of the sepiolite fiber by an electrostatic self-assembly method.
2. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The cement is any one of P·O42.5 grade ordinary Portland cement and P·O52.5 grade ordinary Portland cement; the fine aggregate is river sand with a fineness modulus between 2.4 and 2.8; and the water reducer is any one of polycarboxylic acid water reducer, naphthalene water reducer, and sulfonate water reducer.
3. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The preparation method of the modified sepiolite fiber comprises the following steps: A. Add γ-aminopropyltriethoxysilane to a mixture of deionized water and anhydrous ethanol, stir at 35-45° C. for 2-3 hours to prepare a silane hydrolyzate, then add sepiolite fiber to the silane hydrolyzate, continue stirring for 1.5-2 hours, then take out and dry to prepare pretreated sepiolite fiber; B. Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide dispersion, then adding pretreated sepiolite fiber and adjusting the pH value of the system to 3-4 with hydrochloric acid. The mixture was reacted at 75-85°C for 2-3 hours. After the reaction was completed, the mixture was washed with deionized water and finally heat-treated at 150-165°C for 10-12 hours to prepare modified sepiolite fiber.
4. The crack-resistant and anti-seepage concrete according to claim 3, characterized in that: In step A, the addition ratio of deionized water, anhydrous ethanol and γ-aminopropyltriethoxysilane is 30 mL:70 mL:1.5-2 g; and the addition ratio of the sepiolite fiber and silane hydrolyzate is 5-5.5 g:100 mL.
5. The crack-resistant and anti-seepage concrete according to claim 3, characterized in that: In the step B, the addition ratio of graphene oxide and deionized water is 0.1-0.15 g:100 mL; the addition ratio of the pretreated sepiolite fiber and graphene oxide dispersion is 2-2.5 g:100 mL.
6. The crack-resistant and anti-seepage concrete according to claim 3, characterized in that: The preparation method of the sepiolite fiber comprises the following steps: (1) Ultrasonic dispersion of sepiolite in water, allowing it to soak for 20-24 hours, followed by magnetic stirring for 1-3 hours, allowing it to settle naturally, and filtering the upper suspension, washing it with water, and drying it to obtain crude purified sepiolite; (2) Crude sepiolite was mixed with 3 mol / L hydrochloric acid at a solid-liquid ratio of 1:50, and 20% oxalic acid was added. After stirring, the mixture was placed in an autoclave and subjected to hydrothermal reaction at 190-205°C for 8-9 hours to prepare acidified sepiolite. (3) Freeze the hydrous acidified sepiolite at -20°C to form a solid, thaw it and ultrasonicate it for 0.5-1h, repeat freeze-thaw for more than three times, then wash it until it is neutral, dry it in an oven to constant weight, and then grind it in a grinding jar to make it fluffy, loosen the agglomerated fiber bundles, and prepare sepiolite fiber.
7. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The preparation method of the modified steel fiber comprises the following steps: ① Prepare a mixed solution of ethyl orthosilicate, ethanol and water, and then place it in a water bath at 45-55°C and stir for 4-5 hours to obtain silica sol; ② Prepare a mixed solution of aluminum chloride hexahydrate, ethanol, and water, and then place it in a water bath at 45-55°C and stir for 4-5 hours to obtain aluminum sol; ③ Mix the silica sol and aluminum sol, place in a water bath at 45-55°C and stir for 2-3 hours to obtain a modified glue solution; ④ Pretreat the surface of the steel fiber with sodium hydroxide solution, then soak the pretreated steel fiber in the modified adhesive for 10-30 minutes, then slowly pull the steel fiber out of the modified adhesive at a pulling rate of 1-2 mm / s, finally let it stand to air dry and place it in an oven at 100-120°C for thermal curing for 1-3 hours to prepare the modified steel fiber.
8. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: In step ①, the mass ratio of ethyl orthosilicate, ethanol and water is 10:2:1; in step ②, the mass ratio of aluminum chloride hexahydrate, ethanol and water is 14:10:
10.
9. The crack-resistant and anti-seepage concrete according to claim 1, characterized in that: The mass ratio of silica sol to aluminum sol in step ③ is 7:
2.
10. A method for preparing the crack-resistant and anti-seepage concrete according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: weighing raw materials by weight, adding cement, silica fume, fine aggregate, modified steel fiber and modified sepiolite fiber into a mixer, stirring and mixing, adding water, fly ash and water reducing agent, stirring evenly, and preparing crack-resistant and anti-seepage concrete.